2013
DOI: 10.1016/j.pscychresns.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

APOE associated hemispheric asymmetry of entorhinal cortical thickness in aging and Alzheimer's disease

Abstract: Across species structural and functional hemispheric asymmetry is a fundamental feature of the brain. Environmental and genetic factors determine this asymmetry during brain development and modulate its interaction with brain disorders. The e4 allele of the apolipoprotein E gene (APOE-4) is a risk factor for Alzheimer’s disease, associated with regionally specific effects on brain morphology and function during the life span. Furthermore, entorhinal and hippocampal hemispheric asymmetry could be modified by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 68 publications
7
57
1
Order By: Relevance
“…In general, there was a greater age-related effect on brain structure in the left hemisphere (Davatzikos and Resnick, 2002), particularly in the temporal lobe (Resnick et al, 2003). Existing studies have also suggested that APOEe4 carriers with AD, as well as older cognitively healthy individuals showed thinner entorhinal cortex in the left hemisphere when compared with the right hemisphere (Donix et al, 2013).The disrupted nodal efficiency in the PHG.R in both the functional and WM network may suggest that APOE e4 carriers could develop a more severe AD-related destruction than noncarriers in the PHG.R.…”
Section: The Phg Region and The Lateralizationmentioning
confidence: 95%
“…In general, there was a greater age-related effect on brain structure in the left hemisphere (Davatzikos and Resnick, 2002), particularly in the temporal lobe (Resnick et al, 2003). Existing studies have also suggested that APOEe4 carriers with AD, as well as older cognitively healthy individuals showed thinner entorhinal cortex in the left hemisphere when compared with the right hemisphere (Donix et al, 2013).The disrupted nodal efficiency in the PHG.R in both the functional and WM network may suggest that APOE e4 carriers could develop a more severe AD-related destruction than noncarriers in the PHG.R.…”
Section: The Phg Region and The Lateralizationmentioning
confidence: 95%
“…There are further lines of evidence supporting an enhanced entorhinal structure or activity in healthy adults with young age and a higher atrophy rate as the disease progresses for those risk allele carriers. For instance, healthy APOE ε4 carriers showed a thicker right entorhinal cortex as compared with the left hemisphere (Donix et al, 2013) and a thinner left entorhinal cortex in APOE ε4 carriers than in non-carriers could be identified in children and adolescents (Shaw et al, 2007). Meanwhile, APOE ε4 may lead to an increased activity but greater atrophy in right hemisphere in healthy young subjects (O'Dwyer et al, 2012).…”
Section: Alzheimer's Disease International World Alzheimer Report 20mentioning
confidence: 96%
“…Healthy late-middle aged APOE4 carriers display AD-like brain changes such as, decreased glucose metabolism , brain atrophy ,Donix, et al, 2013,Donix, et al, 2010,Espeseth, et al, 2008,Fan, et al, 2010,Fennema-Notestine, et al, 2011,Julkunen, et al, 2010) and other alterations in task-related and default mode network activity ,Trachtenberg, et al, 2012a,Trachtenberg, et al, 2012b. By the time AD symptoms occur, hippocampal atrophy seems to be a characteristic feature of ApoE ε4 allele carriers (Wolk and Dickerson, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%